2005
DOI: 10.1159/000081244
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Factor V Leiden Mutation in Premature but Not in Full-Term Infants with Grade I Intracranial Haemorrhage

Abstract: Objectives: In the current prospective study our aim was to analyse the distribution of the factor V Leiden (G1691A) mutation in preterm and full-term neonates with grade I intraventricular haemorrhage and in control neonates. Study Method: A group of 125 individually selected neonates with grade I intraventricular haemorrhage and 128 controls were investigated. Results: The allele frequency was 7.2% in the total population of affected infants while it was 3.9% in the controls (p < 0.05); the latter correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
(31 reference statements)
2
12
0
1
Order By: Relevance
“…[31] analyzed a group of 51 newborns with very low weight at birth (22 infants with grade 2 to 4 IVH and 29 in the control group), in which IVH was observed among carriers of the factor V Leiden gene mutation. Similar conclusions were reached by Komlósi et al [18], who observed an increased IVH risk in newborns with congenital thrombophilia and birth weight below 2500 g. However, there are other studies which indicate that factor V Leiden and prothrombin G20210A gene mutations have a protective role against IVH. Data published by Göpel et al [12] show that the risk of IVH above grade 2 among infants carrying factor V Leiden and prothrombin G20210A gene mutations is lower than among those not carrying these mutations.…”
Section: Communicating Authorsupporting
confidence: 84%
“…[31] analyzed a group of 51 newborns with very low weight at birth (22 infants with grade 2 to 4 IVH and 29 in the control group), in which IVH was observed among carriers of the factor V Leiden gene mutation. Similar conclusions were reached by Komlósi et al [18], who observed an increased IVH risk in newborns with congenital thrombophilia and birth weight below 2500 g. However, there are other studies which indicate that factor V Leiden and prothrombin G20210A gene mutations have a protective role against IVH. Data published by Göpel et al [12] show that the risk of IVH above grade 2 among infants carrying factor V Leiden and prothrombin G20210A gene mutations is lower than among those not carrying these mutations.…”
Section: Communicating Authorsupporting
confidence: 84%
“…We found no significant associations with FII or FXIII ; however, the FV Leiden mutation (rs6025) and IVH were strongly associated. The heterozygous genotype of rs6025 was previously shown to associate with an increased risk for IVH and to protect against the extension and/or progression to more severe grades of IVH (14,22). Our study supports these findings as the heterozygous genotype of the FV Leiden mutation was significantly associated in infants with IVH grades I–II ( p =5×10 −3 ) but not IVH grades III–IV ( p =1.0).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IL10 -1082A (rs1800896) is associated with an increased risk of periventricular leukomalacia (PVL), a condition that often occurs in conjunction with IVH (19,20). The coagulation factor V ( FV ) Leiden mutation (rs6025), a coagulation factor II ( FII ) prothrombin polymorphism (G20210A, rs1799963) and a coagulation factor XIII ( FXIII ) missense mutation (Val34Leu, rs5985) have been implicated in several studies as risk factors for the development of IVH (12,14,15,21,22). Additionally, two genes integrin beta-3 ( ITGB3 ) and estrogen receptor-alpha ( ESR1 ) have been associated with IVH (13,23).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of mutation was associated with the severity of IVH [26]. Komlosi et al [6], Aden et al [8], Baier et al [27], Petaja et al [28], and Aronis et al [29] did not find any association mutation of gene FV (Leiden) with IVH in preterm newborns. We did not find any association between FV Leiden mutation and incidence of IVH in preterm infants.…”
Section: Discussionmentioning
confidence: 99%